Review of existing methods of parsing and grammatical text analysis - Abdurakhmanova Umida (Zien Journals, 2021)
This article will cover parsing and grammatical methods. The parsing of the text and its correctness play not the least role in the task of modeling and understanding natural languages. Non-fluctuative languages (English) are especially difficult, in which the spelling of a word does not always guarantee its unambiguous semantic or lexical identification
Keywords: Parsing; grammatical method; analysis; formalism